Ross A. Collins papers - Collins, Ross A. (Ross Alexander), 1880-1968.
Correspondence, speeches, writings, reports, notes, clippings, scrapbooks, printed matter, and other papers relating to Collins's service in the U.S. Congress, especially to his introduction of the bill authorizing the Library of Congress acquisition of the Otto Vollbehr Collection of incunabula. Also documents Collins's work pertaining to the mechanization of the U.S. Army and the development of the B-17 bomber, Mississippi government and politics, the career of Mississippi politician Theodore Gilmore Bilbo, and citizenship in the Choctaw Indian tribe.
U.S. congressman, public official, and lawyer from Mississippi.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bilbo, Theodore Gilmore, -- 1877-1947.; Vollbehr, Otto H. F. -- 1869-; United States. -- Army; Otto Vollbehr Collection (Library of Congress); B-17 bomber; Bombers; Choctaw Indians -- Tribal citizenship; Incunabula; Mechanization, Military; Mississippi -- Politics and government; United States -- Politics and government -- 1933-1953.; Lawyers; Public officials -- Mississippi; Representatives, U.S. Congress -- Mississippi